2020
DOI: 10.1021/acsami.0c00981
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Role of Fluorine in Fully Alkylated Ladder-Type Carbazole-Based Nonfullerene Organic Solar Cells

Abstract: Two fused ladder type non-fullerene acceptors, DTCCIC and DTCCIC-4F, based on an electron-donating alkylated dithienocyclopentacarbazole core flanked by electron-withdrawing non-fluorinated or fluorinated 1,1dicyanomethylene-3-indanone (IC or IC-4F), are prepared and utilized in organic solar cells (OSCs). The two new molecules reveal planar structures and strong aggregation behavior, and fluorination is shown to red shift the optical band gap and down shift energy levels. OSCs based on DTCCIC-4F exhibit a pow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 49 publications
(86 reference statements)
1
41
0
Order By: Relevance
“…Several other studies have demonstrated that fluorinating the NFA, which is a commonly employed method to increase PCEs, can directly impact the BHJ morphology and consequently the recombination and extraction dynamics. [ 29,228–230 ] Favorable morphological features, such as increased atomic‐level local ordering and π–π interactions resolved via ssNMR analyses, were demonstrated in the PTB7‐Th:IOTIC‐4F blend over the nonfluorinated PTB7‐Th:IOTIC‐0F counterpart; consequently, the faster extraction in the PTB7‐Th:IOTIC‐4F blend could be attributed to the morphological effects induced by fluorination alone. [ 29 ] A similar conclusion was reached in a study by Tang et al.…”
Section: Device Performancementioning
confidence: 99%
“…Several other studies have demonstrated that fluorinating the NFA, which is a commonly employed method to increase PCEs, can directly impact the BHJ morphology and consequently the recombination and extraction dynamics. [ 29,228–230 ] Favorable morphological features, such as increased atomic‐level local ordering and π–π interactions resolved via ssNMR analyses, were demonstrated in the PTB7‐Th:IOTIC‐4F blend over the nonfluorinated PTB7‐Th:IOTIC‐0F counterpart; consequently, the faster extraction in the PTB7‐Th:IOTIC‐4F blend could be attributed to the morphological effects induced by fluorination alone. [ 29 ] A similar conclusion was reached in a study by Tang et al.…”
Section: Device Performancementioning
confidence: 99%
“…The effect of fluorinating NFAs is known to be a widely used method to enhance photovoltaic device performances in polymer:NFA blends. [5,[25][26][27][28][29][30] However, because of the structural similarity in the NFAs used, it becomes rather challenging to identify the molecular level origins of this subtle change in molecular structure and its consequent impact on device performances. In fact, while there are several studies in the literature that have utilized ssNMR to characterize blend morphologies for polymers or polymer:fullerene blends, [23,[31][32][33][34][35][36][37] the application of ssNMR techniques to characterize structurally similar polymer:NFA blends is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, introducing the nitrogen atoms form S,N‐heteroarene ladder‐type fused ring cores and replacing sp 3 carbon with sp 2 nitrogen units of A–D–A‐structured small‐molecule acceptors often enhance their possibility to undergo intramolecular charge transfer (ICT) as well as alter their packing orientation. [ 11 ] In this vein, chlorination of the conjugated backbone might be preferable because it is inexpensive, synthetically simple, and higher yielding. [ 12 ] At present, the two main methods to promote charge transport, by accelerating charge dissociation and decreasing charge density at the contact interface, involve 1) extending the fused‐ring conjugated system to enhance the electron‐donating ability and 2) adding a strong electron‐withdrawing group at both ends of the fused ring core to promote electron delocalization.…”
Section: Introductionmentioning
confidence: 99%